2021
DOI: 10.1038/s41598-021-97319-y
|View full text |Cite
|
Sign up to set email alerts
|

An integrated analysis of mRNAs, lncRNAs, and miRNAs based on weighted gene co-expression network analysis involved in bovine endometritis

Abstract: In dairy cattle, endometritis is a severe infectious disease that occurs following parturition. It is clear that genetic factors are involved in the etiology of endometritis, however, the molecular pathogenesis of endometritis is not entirely understood. In this study, a system biology approach was used to better understand the molecular mechanisms underlying the development of endometritis. Forty transcriptomic datasets comprising of 20 RNA-Seq (GSE66825) and 20 miRNA-Seq (GSE66826) were obtained from the GEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…Low-dose ionizing radiation exposure induces downregulation of miR-484 expression in small cell lung cancer cells ( 51 , 52 ). Chronic inflammation stimulates keratin-forming cells and endometrial cells to upregulate miR-484 ( 53 , 54 ).…”
Section: Important Characteristics Of Mir-484mentioning
confidence: 99%
“…Low-dose ionizing radiation exposure induces downregulation of miR-484 expression in small cell lung cancer cells ( 51 , 52 ). Chronic inflammation stimulates keratin-forming cells and endometrial cells to upregulate miR-484 ( 53 , 54 ).…”
Section: Important Characteristics Of Mir-484mentioning
confidence: 99%
“…In agreement with the main hypothesis of this study, M. bovis infection in bAMs was able to change the network characteristics of 67% of the identified modules (14 out of 21) compared to the non-infected control bAMs. Then, functional enrichment analysis based on the biological processes and KEGG pathways showed that among the 14 non-preserved modules, 7 non-preserved modules, including blue, brown, green, pink, salmon, tan, and turquoise were directly involved in host-pathogen interactions and could be important candidates for studying pathogenic mechanisms of bTB as in previous similar studies, these candidate non-preserved modules were successfully used as key modules to describe the complex etiology of several bovine diseases, such as bovine mastitis ( Bakhtiarizadeh et al, 2020 ), bovine respiratory disease (BRD; Hasankhani et al, 2021b ), bovine endometritis ( Sheybani et al, 2021 ), and Johne’s disease ( Heidari et al, 2021 ). It should be noted that loss of connection or alteration of the connectivity patterns and network density in the non-preserved modules can be attributed to the abnormal expression of several genes in M. bovis -infected conditions, which can be key factors in the development of bTB.…”
Section: Discussionmentioning
confidence: 95%
“…Mutations within the CCDC40 are associated with cilia and sperm dysmotility [ 72 ], and are suspected to be involved in idiopathic male infertility [ 64 ]. Moreover, co-expression and interactions between lncRNAs and the CCDC40 and ZMYND10 are involved in bovine endometritis [ 73 ]. These distant examples demonstrate that those genes are prone to the regulatory function of the lncRNAs.…”
Section: Discussionmentioning
confidence: 99%